THE IMPORTANCE OF SELF-EMOTIONAL COMPETENCY MODEL FOR MIDDLE SCHOOL LEADERS IN THE ERA OF SOCIETY 5.0: A PILOT STUDY - Norliza Samad; Mohd Asri Mohd Noor; Mahaliza Mansor, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The self-emotional competency model can be used as a measurement tool to increase the emotional qualities of school leadership in facing the change in the education era of Society 5.0. However, validation of the self-emotional competency model using exploratory factor analysis (EFA) is still scarce. Therefore, this pilot study is conducted to identify the applicability of the emotional competency model of middle leaders in primary schools through exploratory factor analysis (EFA). This study employed a quantitative approach using a survey method. A questionnaire was used as a research instrument. The instrument contained 18 items. A total of 179 respondents participated in this pilot study. The validity and reliability of the instrument were obtained through descriptive analysis of Cronbach's Alpha reliability and exploratory factor analysis (EFA) using SPSS version 27 software. The overall analysis shows that 13 items meet the EFA fit requirements with Kaiser-Meyer-Olkin (KMO) values of more than 0.6. Bartlett's test values were significant, with item communalities values exceeding 0.3 and Eigen values exceeding 1.0 at a percentages of variance exceeding 60 percent. The Cronbach's Alpha coefficient was above 0.70 for all items. A total of five items were removed. The findings of the study show that the instrument of self-emotional competency instrument has very high validity and reliability and has the potential to be used as a guide in the development of self-emotional competence of middle leaders in Malaysia. A positive impact is essential in generating emotionally intelligent leaders who are competitive and capable to lead the school community towards the era of Society 5.0 especially in primary school in Malaysia.